Current Topics in Functional Food - Shiomi, Naofumi; Savitskaya, Anna (IntechOpen, 2022)
The market for functional foods is steadily expanding as more people worldwide realize the value of the daily consumption of healthy foods in maintaining good health. Recent studies have revealed new functional compounds in foods. Genetically modified foods will soon be commercially available. This book discusses the characteristics of functional foods and the health benefits of ingredients including ginger, herbs, probiotics, mushrooms, and dairy products. It also provides new ideas for the production of new functional foods and managing health through the daily diet.